Assistance for Disaster-Responsive and Resilient Urban Village through the Implementation of Appropriate Technologies: Infiltration Wells, Biopores, and Clean and Healthy Living Behavior (PHBS) - Rokhmalia, Fitri; Khambali; Rachmaniyah; Edi, Imam Sarwo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Indonesia’s population growth more than 273 m in 2021, has brought various environmental challenges, particularly in urban areas such as Surabaya. Jambangan Urban Village, with over 52,000 residents, faces issues of flooding and fire hazards due to limited green open spaces, inadequate drainage, and insufficient emergency facilities. Moderate rainfall often leads to flooding, while in 2017 a major fire incident destroyed houses and workshops because of the lack of pumps and hoses to access nearby river water before firefighters arrived. These conditions highlight the urgent need for integrated disaster preparedness and environmental management. Community service initiatives have been carried out in Jambangan to address these challenges. The infiltration wells 3 units has contributed to flood reduction and groundwater conservation. Waste management activities, led by community organizations such as W Queen, have supported environmental preservation and the vision of a flood-free tourism village. Additionally, the introduction technologies biopores, infiltration wells, and Clean and Healthy Living Behavior (PHBS) practices, including proper handwashing and oral health maintenance has improved community awareness and resilience. The outputs of this program include academic publication in an indexed international journal and the development of intellectual property products such as educational leaflets and documentary videos on disaster preparedness. The outcomes for community partners are significant: reducing flood risks, improving firefighting readiness, strengthening knowledge of appropriate technologies, and promoting healthier lifestyles. Ultimately, the active participation of the community in water conservation, waste management, and disaster response is essential to building a resilient and sustainable urban environment in Surabaya.